2015
DOI: 10.3844/ajeassp.2015.210.222
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility Study on Solar Power Plant Utility Grid under Malaysia Feed-in Tariff

Abstract: Abstract:In Perlis, Northern Malaysia, a solar power plant with an energy capacity of 5 MWp began selling energy to Tenaga Nasional Berhad in January 2013. Upon obtaining Feed-in Tariff approval from the Sustainable Energy Department Authority of Malaysia, the power plant will produce energy with a Feed-in Tariff of RM 0.874 for every kWh for 21 years according to the Renewable Energy Power Purchase Agreement. However, the output of solar plants is unpredictable. Investors commonly estimate the output of solar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Grid emission was also considered in this study. The values of carbon dioxide, sulfur dioxide, and nitrogen oxides were considered as 632 g/kWh, 2.74 g/kWh, 1.34 g/kWh, respectively [43,44].…”
Section: External Power Gridmentioning
confidence: 99%
“…Grid emission was also considered in this study. The values of carbon dioxide, sulfur dioxide, and nitrogen oxides were considered as 632 g/kWh, 2.74 g/kWh, 1.34 g/kWh, respectively [43,44].…”
Section: External Power Gridmentioning
confidence: 99%
“…The financial assumptions for this plant are presented in Table 3. The initial cost for the plant is assumed as MYR 40 million [10] with operation and maintenance cost MYR 100,000 while the inflation rate is taken as 3%.…”
Section: The Proposed 5 Mw Plantmentioning
confidence: 99%
“…In order to assist the government's goal of reducing carbon emission intensity, MESTECC) has formed a variety of solar energy policies initiatives with various parties, including the residential and industrial sectors.In Malaysia, a number of studies evaluating the performance of PV installations have been conducted (see examples [8] [18]). All of these studies reported on solar PV performance metrics (such as performance ratio and involved sector), which vary with solar energy legislation, as shown in Table 2.…”
mentioning
confidence: 99%